2018
DOI: 10.3835/plantgenome2018.03.0017
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Challenges of Applied Genomic Selection—A New Paradigm in Breeding for Grain Yield in Bread Wheat

Abstract: Core Ideas Genomic prediction of grain yield across nurseries or years is challenging, because of genotype × environment interactions. Prediction accuracies can be improved by having at least one full‐sib in the training population. Genomic selection (GS) was less advantageous for within‐family selections in elite families with few full‐sibs and minimal Mendelian sampling variance. It is important to apply GS at the appropriate stage of the breeding cycle. Genomic selection (GS) has been promising for increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 99 publications
(200 reference statements)
6
74
1
Order By: Relevance
“…Using the more related DH panels as test sets resulted in higher prediction accuracy compared with using the F5 in the presence of SRI as fixed effects (mean prediction accuracy of 0.23 vs. 0.15), indicating the relevance of relatedness between the training and validation panels. This is consistent with previous studies that show the importance of using genetically related populations for predictions [27,47,48]. Our results further indicate that when genetically unrelated populations are used for genomic predictions, the inclusion of secondary traits in the model could increase prediction accuracy for grain yield.…”
Section: Genomic Prediction For Grain Yieldsupporting
confidence: 92%
“…Using the more related DH panels as test sets resulted in higher prediction accuracy compared with using the F5 in the presence of SRI as fixed effects (mean prediction accuracy of 0.23 vs. 0.15), indicating the relevance of relatedness between the training and validation panels. This is consistent with previous studies that show the importance of using genetically related populations for predictions [27,47,48]. Our results further indicate that when genetically unrelated populations are used for genomic predictions, the inclusion of secondary traits in the model could increase prediction accuracy for grain yield.…”
Section: Genomic Prediction For Grain Yieldsupporting
confidence: 92%
“…Although poor predictive ability remains a major challenge in implementing genomic selection (Crossa et al, 2014), several studies have shown that genomic selection could be advantageous for complex traits with low heritability such as grain yield (Belamkar et al, 2018;Burgueño et al, 2012;. Genomic selection with low to moderate levels of predictive ability could be used in early-generation testing and selection (Belamkar et al, 2018;Juliana et al, 2018;Michel et al, 2018) and in off-season nurseries where field phenotypic information might be useless. Breeding program do not rely on predictive ability itself, but also on how genomic selection can be leveraged in selecting or discarding lines within a program, selecting parents, and phenotyping efforts (Belamkar et al, 2018;Juliana et al, 2018;Lado et al, 2018).…”
Section: Trait Characterization and Associationmentioning
confidence: 99%
“…Genomic selection with low to moderate levels of predictive ability could be used in early-generation testing and selection (Belamkar et al, 2018;Juliana et al, 2018;Michel et al, 2018) and in off-season nurseries where field phenotypic information might be useless. Breeding program do not rely on predictive ability itself, but also on how genomic selection can be leveraged in selecting or discarding lines within a program, selecting parents, and phenotyping efforts (Belamkar et al, 2018;Juliana et al, 2018;Lado et al, 2018).…”
Section: Trait Characterization and Associationmentioning
confidence: 99%
“…The implementation of genomic selection in many national and international plant breeding programmes in recent years (Guzmán et al 2016 ; Lado et al 2016 ; Michel et al 2016 ; Cericola et al 2017 ; Belamkar et al 2018 ; Juliana 2018 ) highlights the potential of this new breeding tool for variety development and accelerating the genetic improvement in crop plants. The merit of employing genomic predictions has been frequently tested by cross-validation, but also across families and years taking genomic relationship and genotype-by-environment interaction into account (Gezan et al 2017 ; Ben Hassen et al 2018 ; Kristensen et al 2018 ; Huang et al 2018; Pembleton et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%